How federal agencies can secure their cloud migrations. (July 2015) - McKenna, Matthew
Abstract : The cloud offers increased efficiencies and cost savings, and the US Federal Government has taken notice. A massive migration to commercial cloud services is underway, and it's no mean feat. It necessitates the creation and implementation of a migration strategy that moves selected new and legacy functions to cloud technology without disruption – and with maximum security. In the US, FedRAMP was created to make the cost-saving cloud migration for federal agencies both safe and hopefully stress-free. But IT admins must make a commitment to strong key management and effective monitoring of their encrypted networks in order to build on FedRAMP's foundation, says Matthew McKenna of SSH Communication Security.